Stock Returns and Liquidity Changes Around the Screening Announcement: An Empirical Study in Indonesia - D. Y. Rahmasuciana; A. Alwahidin; A. S. Utomo; Muhammad Rofi'i (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2015)
This paper aims to identify and analyze the volatility of stock returns and the changes of liquidity around the announcement of Shari’ah stock screening published by Otoritas Jasa Keuangan (OJK) and Dewan Syariah Nasional (DSN-MUI). The announcement is consist of stocks that become the constituent of ISSI (Indonesia Shari’ah Stock Index) and the stocks out from ISSI in each period. The number of data are 341 emitens, divided into two categories. The first category was 196 stocks that out from the composition of ISSI, and the second was shari’ah stock from 145 emitens which categorized as part of ISSI from 2011 to 2016. The statistical method (t-test) is used to analyze the change of stock returns and the change of liquidity in 14 days around the announcement (6 days pre- and post announcement). The result shows that Shari’ah compliant stocks over 6 years around the announcement have no difference in return and have negative sign for both the Shari’ah stocks and the stocks out from ISS. It may caused by the intention of Islamic investor which invest their capital based on the compliance of Shari’ah, so the returns do not become the most important one. Interestingly, on the other hand, the liquidity change of stocks which out of ISSI has negative significant difference on the days after the announcement of screening. It indicates that the non-compliant stocks have negative in change of liquidity or have significant liquidity declining after the announcement. Also, in fact Islamic invetors are more concern in the list of stocks that out from ISSI and the stock returns become less important to them than the compliance of investment. Thess findings confirm the issue that the screening is not effecting the expected return of investors. Besides, this study tells that the screening is perceived as important information by the investors in making decisions. Thus, the next studies are needed to investigate the effect of long-term investment on shari’a stock and the factors that influence the shari’a stock return during the period of announcement.